Cu-Hemin Nanosheets and Indocyanine Green Co-Loaded Hydrogel for Photothermal Therapy and Amplified Photodynamic Therapy - Zhu, Shu; Wang, Shuntao; Liu, Chunping; Lyu, Meng; Huang, Qinqin (Frontiers in Oncology, 2022)
Near-infrared (NIR) organic small molecule indocyanine green (ICG) could respond well to 808 nm laser to promote local high temperature and ROS generation for realizing photothermal therapy (PTT)/photodynamic therapy (PDT). However, the high content of GSH in the tumor microenvironment (TME) limited the further therapeutic performance of ICG. Herein, injectable agarose in situ forming NIR-responsive hydrogels (CIH) incorporating Cu-Hemin and ICG were prepared for the first time. When CIH system was located to the tumor tissue through local injection, the ICG in the hydrogel could efficiently convert the light energy emitted by the 808 nm laser into thermal energy, resulting in the heating and softening of the hydrogel matrix, which releases the Cu-Hemin. Then, the over-expressed GSH in the TME could also down-regulated by Cu-Hemin, which amplified ICG-mediated PDT. In vivo experiments validated that ICG-based PDT/PTT and Cu-Hemin-mediated glutathione depletion could eliminate cancer tissues with admirable safety. This hydrogel-based GSH-depletion strategy is instructive to improve the objective response rate of PDT.